ROS Induce β-Carotene Biosynthesis Caused by Changes of Photosynthesis Efficiency and Energy Metabolism in Dunaliella salina Under Stress Conditions - Xi, Yimei; Kong, Fantao; Chi, Zhanyou (Frontiers in Bioengineering and Biotechnology, 2021)
The unicellular alga Dunaliella salina is regarded as a promising cell factory for the commercial production of β-carotene due to its high yield of carotenoids. However, the underlying mechanism of β-carotene accumulation is still unclear. In this study, the regulatory mechanism of β-carotene accumulation in D. salina under stress conditions was investigated. Our results indicated that there is a significant positive correlation between the cellular ROS level and β-carotene content, and the maximum quantum efficiency (Fv/Fm) of PSII is negatively correlated with β-carotene content under stress conditions. The increase of ROS was found to be coupled with the inhibition of Fv/Fm of PSII in D. salina under stress conditions. Furthermore, transcriptomic analysis of the cells cultivated with H2O2 supplementation showed that the major differentially expressed genes involved in β-carotene metabolism were upregulated, whereas the genes involved in photosynthesis were downregulated. These results indicated that ROS induce β-carotene accumulation in D. salina through fine-tuning genes which were involved in photosynthesis and β-carotene biosynthesis. Our study provided a better understanding of the regulatory mechanism involved in β-carotene accumulation in D. salina, which might be useful for overaccumulation of carotenoids and other valuable compounds in other microalgae.